ETHNICITY AND ETHNIC REVIVALISM INTERNATIONALLY AND IN AFRICA TODAY - Bloom, J.B. (Scientia Militaria - South African Journal of Military Studies, 2012)
As a continuing and powerful force on the world stage of the eighties ethnic revivalism shows few signs of being a spent force. First remarked on by social commentators only within the last two decades, ethnicity remains a worldwide phenomenon. A bewildering number of hitherto ignored and. unknown nationalities and ethnic groupings continue to gain media attention, their demands ranging from outright secession and full independence to calls for non-discriminatory treatment and requests for language rights, cultural grants, broadcasting time etc. At its most dramatic, various terrorist stunts draw media attention to the alleged plight of some oppressed minority, but in more peaceful ways too, governments have fallen and constitutional crises been created due to the electoral and other influence of increasingly vociferous ethnic minority groupings.